2017
DOI: 10.1002/jcp.25908
|View full text |Cite
|
Sign up to set email alerts
|

Reduced glucose‐induced insulin secretion in low‐protein‐fed rats is associated with altered pancreatic islets redox status

Abstract: In the present study, we investigated the relationship between early life protein malnutritioninduced redox imbalance, and reduced glucose-stimulated insulin secretion. After weaning, male Wistar rats were submitted to a normal-protein-diet (17%-protein, NP) or to a low-protein-diet (6%-protein, LP) for 60 days. Pancreatic islets were isolated and hydrogen peroxide (H 2 O 2 ), oxidized (GSSG) and reduced (GSH) glutathione content, CuZn-superoxide dismutase (SOD1), glutathione peroxidase (GPx1) and catalase (CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 44 publications
(72 reference statements)
1
22
0
Order By: Relevance
“…Plasma estradiol levels in females may be endangered from insulin deficiency by inhibiting oxidative stress (Yokomizo et al, 2014). The susceptibility of pancreatic islets to oxidative stress is credited to their low level of expression of antioxidant enzymes (Lenzen et al 1996) such as SOD1 (Cappelli et al 2018), SOD2 (superoxide dismutase 1,2) and catalase (Takahashi et al 2014). The genetic association of SOD2 with type II diabetes has been described (Miao et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Plasma estradiol levels in females may be endangered from insulin deficiency by inhibiting oxidative stress (Yokomizo et al, 2014). The susceptibility of pancreatic islets to oxidative stress is credited to their low level of expression of antioxidant enzymes (Lenzen et al 1996) such as SOD1 (Cappelli et al 2018), SOD2 (superoxide dismutase 1,2) and catalase (Takahashi et al 2014). The genetic association of SOD2 with type II diabetes has been described (Miao et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported changes in antioxidant enzymes activity and reactive oxygen species concentration in islets from protein malnourished rodents [16,17]. However, studies investigating the effects of amino acid restriction on beta cell viability are still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress leads to many diseases, such as sepsis and enteritis, in young animals [1,2]. Earlyweaned pigs suffer oxidative challenges that produce large amounts of reactive oxygen species (ROS) [3].…”
Section: Introductionmentioning
confidence: 99%